2002
DOI: 10.1103/physrevlett.89.263004
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Angular Momentum Composition of a Rydberg Electron Wave Packet

Abstract: Sequences of phase-locked laser pulses have been employed to control the orbital angular momentum character of an electron wave packet, which is initially created from a superposition of s and d Rydberg series. By an intelligent choice of phase, which depends on the excitation energy and the quantum defects, we are able to selectively pump down either all or a fraction of one or other angular momentum component, and by employing multichannel quantum-defect theory we are able to analyze the quantum-state distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
31
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 17 publications
(15 reference statements)
0
31
0
Order By: Relevance
“…However, Rydberg electron dynamics is slower and occurs on the order of picoseconds. Rydberg states play an important role in many gas phase chemical processes, and tunable Rydberg wave packets in atoms have been used widely to examine fundamental phenomena; examples include nondispersing Bohr wave packets [16], coherent control [17], and high harmonic generation [18]. In a prescient article, Wilson et al [19] suggested that Rydberg wave packets in hydrogen atoms could be imaged using x-ray diffraction, with the electron wave packet forming a natural diffraction grid for the x-ray photon.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, Rydberg electron dynamics is slower and occurs on the order of picoseconds. Rydberg states play an important role in many gas phase chemical processes, and tunable Rydberg wave packets in atoms have been used widely to examine fundamental phenomena; examples include nondispersing Bohr wave packets [16], coherent control [17], and high harmonic generation [18]. In a prescient article, Wilson et al [19] suggested that Rydberg wave packets in hydrogen atoms could be imaged using x-ray diffraction, with the electron wave packet forming a natural diffraction grid for the x-ray photon.…”
mentioning
confidence: 99%
“…Excitation to the J ¼ 1 Rydberg states can be achieved via single-photon excitation or via a resonant multiphoton process with a J ¼ 0 intermediate state [17,34]. Figure 2 shows the proportional contribution of each of the five channels to the total wave packet as a function of time, via the probability P j;r>r c ðtÞ in Eq.…”
mentioning
confidence: 99%
“…Similar twopulse schemes have also been used for coherent control in a number of experiments. [21][22][23] This is, to the best of our knowledge, the first full quantum simulation of a multiple-pulse control processes that allows us to map the dynamics inside and outside the molecule. Specifically, we examine two examples of pulse sequences; in the first instance we double the characteristic beating frequency of a Rydberg wave packet by removal of every other state, and in the second we control the amount of autoionization by selective pumping of the autoionizing wave packet, thereby changing the ionization yield by up to 84%.…”
Section: Introductionmentioning
confidence: 99%
“…nl ÿ1=2 n ÿ l 2 is its frequency and a nl is its amplitude in the superposition. After an integer number of orbit periods k, each wave packet, corresponding to a channel l, accumulates a phase 2 k l , resulting in an accumulated phase difference between the two wave packets, l 2 k l [13]. The accumulated phase difference between two Rydberg series was recently exploited to control the orbital angular momentum composition of an atomic electron wave packet.…”
mentioning
confidence: 99%
“…Phase-shaped pulses have been employed to excite arbitrary wave packets [7] and to fully characterize their amplitude and phase profile [8][9][10]. Intuitive schemes exploiting trains of phase-locked optical pulses have been employed to create Schrö dinger's cat states [11], to demonstrate Young's double slit interference in an atom [12], to control electronic orbital angular momentum [13], and the radial distribution [14]. In this Letter, we take a step further and develop an intuitive scheme to control the dynamics of a molecular system.…”
mentioning
confidence: 99%